The effect of adalimumab on key drivers in the pathogenesis of psoriasis3. (March 2014) - Hendriks, A.G.M.; van der, H.M.J.; Wolberink, E.A.W.; Seyger, M.M.B.; Schalkwijk, J.; Zeeuwen, P.L.J.M.; de, E.M.G.J.; Pasch, M.C.; van, P.E.J.; van de, P.C.M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Recently introduced biologics targeting specific immune mechanisms have identified crucial steps in the pathogenesis of psoriasis. What does this study add? During adalimumab treatment markers of epidermal differentiation, proliferation and the innate immune system revert rapidly to normal, well before changes in the adaptive immune system become apparent.